Magnetic transition and defect characteristics of multiferroic CuFe1-xGaxO2 studied by positron annihilation spectra. (December 2018) - Zhang, L.; Xiong, D.K.; Goodman, B.A.; Chen, Z.P.; Deng, W.; Huang, Y.Y.
Graphical abstract: Highlights: A systematic investigation of the effect of Ga doping on the structural and magnetic properties of CuFeO2 . Crystal defects are determined by positron annihilation spectroscopy. There is a good correlation between antiferromagnetic stability and lattice distortion. Crystal defects and interlayer ions in polycrystalline samples influence the magnetic properties. Abstract: The structure, crystal defects and magnetic properties of multiferroic CuFe1- x Ga x O2 (CFGO; x  = 0–0.07) ceramics are studied systemically. Substitution of Ga 3+ for Fe 3+ shrinks the CFO lattice, decreases the particle size, and causes small liquid phase formation. Positron annihilation spectroscopy demonstrates that all samples contain a considerable number of vacancy defects. The overall defect environment is virtually unaffected by Ga 3+ doping, but the open-volume of the defects is redistributed. Magnetic susceptibility measurements show that Ga doping enhances the strength of the antiferromagnetic interaction between high-spin Fe 3+ ions as a result of reduced magnetic correlation length, but decrease the stability of the antiferromagnetic phase. The antiferromagnetic transition temperature, T N2, decreases from 11 K for x  = 0 to 8 K for x  = 0.07, and this destabilization of the antiferromagnetic phase is closely related to the crystal structure and defects, which are discussed in detail in this work.